2020
DOI: 10.1016/j.jhtm.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Airbnb prices according to property/room type, season and location: A regression approach

Abstract: While past studies on Airbnb pricing highlight the importance of room features, host characteristics and location factors, little has been investigated about whether these factors are the same across different property/room types, locations and seasons. To fill that gap, this paper presents a study about the drivers of Airbnb prices in Bristol using ordinary least squares (OLS) and geographically-weighted regression (GWR) methods. The estimated models exhibit sharply different levels of goodness-of-fit, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Due the growing relevance of the sharing economy in the hospitality industry, there has been a proliferation of studies trying to shed light on a number of issues related to this phenomenon, such as host pricing strategies (Gibbs et al, 2018a(Gibbs et al, , 2018bVoltes-Dorta and Sanchez-Medina, 2020), hosts-guests relationships (Casais et al, 2020;Apostolidis and Brown, 2021), trust, reputation, brand loyalty, and various antecedents and consequences of consumer behavior in sharing economy platforms (e.g., Ert et al, 2016Ert et al, , 2019Benoit et al, 2017;Liang et al, 2018;Lutz and Newlands, 2018;Mahadevan, 2018;Abrate and Viglia, 2019;Ert et al, 2019;Mody et al, 2019;Mao et al, 2020;Mody and Hanks, 2020;Suess et al, 2020;Xie et al, 2020;Xu and Gursoy, 2020;Lim et al, 2021;Pitt et al, 2021). Other studies have examined sharing economy regulation issues (Grimmer et al, 2019;Yang and Zhenxing, 2020;Yeon et al, 2020), as well as the effects of sharing economy entry on incumbents' profitability, survival, employment, and ability to secure investments (Zervas et al, 2015;Neeser, 2015;Fang et al, 2016;Zervas et al, 2017;Dogru et al, 2017;Hajibaba and Dolnicar, 2017;Blal et al, 2018;Heo et al, 2019;Li and Srinivasan, 2019;de Lange and Valliere, 2020;Sainaghi and Baggio, 2020;Mat...…”
Section: Literature Background On Sharing Economymentioning
confidence: 99%
“…Due the growing relevance of the sharing economy in the hospitality industry, there has been a proliferation of studies trying to shed light on a number of issues related to this phenomenon, such as host pricing strategies (Gibbs et al, 2018a(Gibbs et al, , 2018bVoltes-Dorta and Sanchez-Medina, 2020), hosts-guests relationships (Casais et al, 2020;Apostolidis and Brown, 2021), trust, reputation, brand loyalty, and various antecedents and consequences of consumer behavior in sharing economy platforms (e.g., Ert et al, 2016Ert et al, , 2019Benoit et al, 2017;Liang et al, 2018;Lutz and Newlands, 2018;Mahadevan, 2018;Abrate and Viglia, 2019;Ert et al, 2019;Mody et al, 2019;Mao et al, 2020;Mody and Hanks, 2020;Suess et al, 2020;Xie et al, 2020;Xu and Gursoy, 2020;Lim et al, 2021;Pitt et al, 2021). Other studies have examined sharing economy regulation issues (Grimmer et al, 2019;Yang and Zhenxing, 2020;Yeon et al, 2020), as well as the effects of sharing economy entry on incumbents' profitability, survival, employment, and ability to secure investments (Zervas et al, 2015;Neeser, 2015;Fang et al, 2016;Zervas et al, 2017;Dogru et al, 2017;Hajibaba and Dolnicar, 2017;Blal et al, 2018;Heo et al, 2019;Li and Srinivasan, 2019;de Lange and Valliere, 2020;Sainaghi and Baggio, 2020;Mat...…”
Section: Literature Background On Sharing Economymentioning
confidence: 99%
“…Typical accommodation characteristics that influence prices are distance to the beach, the city centre, tourism hotspots, train stations or airports (Castro and Ferreira 2018;Gunter and Önder 2018;Soler-García and Gémar-Castillo 2018), as well as reputational factors such as hotel brand, number of stars and customer ratings (Castro and Ferreira 2018;Soler-García et al 2019). Additional features affecting prices are hotel category; availability of a swimming pool, fitness centre or sport facilities (Castro and Ferreira 2018); pet admission (Santos et al 2021); spa; parking; accommodations' size (Chen and Rothschild 2010;Santos et al 2021;Voltes-Dorta and Sánchez-Medina 2020); the inclusion of a restaurant, bar or terrace; and room amenities such as Wi-Fi, television (TV), minibar or room service (Castro and Ferreira 2018).…”
Section: Efficient Pricingmentioning
confidence: 99%
“…A significant number of studies have found that property, host and location factors have the strongest impact on prices (Voltes-Dorta and Sánchez-Medina 2020). Significant property features usually include the number of beds, bedrooms and bathrooms (Fearne 2021;Gibbs et al 2018;Gunter and Önder 2018;Voltes-Dorta and Sánchez-Medina 2020) and online photos (Tong and Gunter 2020). Host characteristics, reputation, experience, responsiveness and 'superhost' status are specifically referred to in research on Airbnb (Gunter and Önder 2018;Voltes-Dorta and Sánchez-Medina 2020).…”
Section: Efficient Pricingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various criteria can be found in the literature for analysing the trend of prices of accommodation facilities [7,8]. They can be grouped into the following categories: a) Seasonality; b) Spatial factor; c) e-wom; d) Influence of reviews; e) Combination of several factors.…”
Section: Related Workmentioning
confidence: 99%